2015
DOI: 10.1021/acsnano.5b05927
|View full text |Cite
|
Sign up to set email alerts
|

Weak Van der Waals Stacking, Wide-Range Band Gap, and Raman Study on Ultrathin Layers of Metal Phosphorus Trichalcogenides

Abstract: 2D semiconducting metal phosphorus trichalcogenides, particularly the bulk crystals of MPS3 (M = Fe, Mn, Ni, Cd and Zn) sulfides and MPSe3 (M = Fe and Mn) selenides, have been synthesized, crystallized and exfoliated into monolayers. The Raman spectra of monolayer FePS3 and 3-layer FePSe3 show the strong intralayer vibrations and structural stability of the atomically thin layers under ambient condition. The band gaps can be adjusted by element choices in the range of 1.3-3.5 eV. The wide-range band gaps sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
497
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 458 publications
(545 citation statements)
references
References 50 publications
(57 reference statements)
28
497
0
6
Order By: Relevance
“…Van der Waals (vdW) heterostructures composed of 2D layered materials have been attempted intensively recently due to the novel physical properties covering a wide range of electronic, optical, and optoelectronic systems 198, 199, 200, 201, 202, 203, 204, 205, 206, 207, 208, 209, 210, 211, 212, 213, 214, 215, 216, 217, 218, 219, 220, 221, 222, 223, 224, 225, 226, 227, 228, 229, 230, 231, 232, 233, 234, 235, 236, 237, 238, 239, 240, 241, 242. Jo and co‐workers130 synthesized polymorphic 2D tin‐sulfides of either p‐type SnS or n‐type SnS 2 via adjusting hydrogen during the process.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…Van der Waals (vdW) heterostructures composed of 2D layered materials have been attempted intensively recently due to the novel physical properties covering a wide range of electronic, optical, and optoelectronic systems 198, 199, 200, 201, 202, 203, 204, 205, 206, 207, 208, 209, 210, 211, 212, 213, 214, 215, 216, 217, 218, 219, 220, 221, 222, 223, 224, 225, 226, 227, 228, 229, 230, 231, 232, 233, 234, 235, 236, 237, 238, 239, 240, 241, 242. Jo and co‐workers130 synthesized polymorphic 2D tin‐sulfides of either p‐type SnS or n‐type SnS 2 via adjusting hydrogen during the process.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…The previous reports indicated that the band gaps of these MPX 3 bulks range from 1.3 to 3.5 eV,13 suggesting the light absorption at a wide wavelength for photocatalysts.…”
mentioning
confidence: 91%
“…[20] MPTs have been predicted to be exfoliated more easily from the bulk due to their lower cleavage energy relative to that of graphite, and a lower formation energy than that of MoS 2 . [19] Chu et al fabricated a UV photodetector from nickel phosphorus trichalcogenide (NiPS 3 ) that had a rise time shorter than 5 ms, a dark current less than 10 fA, and a 254-nm detectivity of 1.22 × 10 12 Jones. [19] Chu et al fabricated a UV photodetector from nickel phosphorus trichalcogenide (NiPS 3 ) that had a rise time shorter than 5 ms, a dark current less than 10 fA, and a 254-nm detectivity of 1.22 × 10 12 Jones.…”
Section: Introductionmentioning
confidence: 99%